Fitness testing parameters for Alpine ski racing - Pritchard, J. J. (Strength and Conditioning Journal, 2021)
Alpine ski racing requires high levels of isometric, eccentric, and concentric muscle actions through wide ranges of hip, knee, and ankle mobility. The course duration of ~40 seconds for slalom racing to upward of 2.5 minutes for downhill racing necessitates high levels of anaerobic endurance, aerobic power, and force production to be successful. In addition, due to the highly technical skill aspect of ski racing, neuromuscular coordination is of utmost importance. This review identifies the most effective performance testing methods for alpine ski racing, as well as highlighting their relevance to the physiological parameters of the sport.